Holistic perspective for investments in agricultural drainage in Egypt - Wahba, M. A. S., author; Amer, M. H., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
During the last 30-40 years, Egypt has implemented one of the largest drainage networks in the world, consisting of surface drains, subsurface drains, pump stations and other related works. The target area to be provided with subsurface drainage in Egypt is 6.4 million acres out of which about 5.5 million acres is already implemented. Subsurface drainage systems in Egypt have reached the stage that more areas installed have, in theory, passed their economic lifetime and these areas need rehabilitation. The overall cost of installation of subsurface drainage in Egypt is estimated at EGP 1600 per acre (year 2007), and about EGP 900 per acre for rehabilitation of old drainage systems. Maintenance costs are estimated at EGP 50 per acre per year. The pay back period of drainage is not more than 3-4 years. Incremental benefits of improved drainage on productivity amount to US $ 250 — 350, per hectare depending on location and soils. Recently, a new role for drainage as a complementary part of the integrated water resources management has been recognized and the benefits of drainage went beyond reducing soil salinity and increasing crop yields. For that reason a new view for the drainage investment is needed which take into consideration all the benefits and impacts and the expected changes in all levels of planning, implementing, operating, maintaining and managing the new and old drainage systems. The objective of this paper is to identify the current and future investments of agriculture drainage for a sustainable agricultural production in Egypt. In spite of the great achievements and benefits of drainage in Egypt, there is a huge potential for investments are needed to sustain agricultural drainage against the future challenges.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.